الاثار الاجتماعية لمحاكم التفتيش على الموريسكيين - خنيش سعيدة; اشراف: مصطفى بن حسين (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
الاثار الاجتماعية لمحاكم التفتيش على الجالية المسلمة كان لمحاكم التفتيش الاسبانية،التي تأسست في اواخر القرن الخامس عشر،عواقب اجتماعية وخيمةعلى المجتمع الاسلامي في اسبانيا،وخاصة الموريسكيين الذين اجبروا على اعتناق المسيحية .كان هدفها الرئيسي هو التجانس الديني، مما مزق النسيج الاجتماعي للمجتمعات الاسلامية التي ازدهرت لقرون. كان من اهم اثارها انحلال التماسك المجتمعي ،وتزايد الرقابة على الاحياء الاسلامية،التي كانت في السابق مراكز للحياة الثقافية و الدينية ،مما ادى الى انعدام الثقة بين افراد المجتمع. كما اجبر الخوف من التعذيب الكثيرين على اخفاء ممارساتهم الدينية ،مما خلق مناخا من السرية والشك .حيث قيدت التجمعات الاجتماعية والطقوس الدينية والعادات التقليدية ،مما اضعف الروابط المجتمعية. كما تسببت محاكم التفتيش في تفكك الاسرة ،وذلك بسجن العديد من الموريسكيين اونفيهم او اعدامهم ،مما ترك اسرا مفككة وغير مستقرة.حيث نشا الاطفال في خوف دائم،وغالبا ماكانوا يتلقون تعليما مسيحيا بدلا من تعاليم اجدادهم الاسلامية. اذ ادت ضغوط الزواج المختلط والتحولات القسرية الى تغيير هياكل الاسرة ،مما ادى الى تراجع الاعراف الاجتماعية التقليدية. ومن الاثار المهمة الاخرى تهميش الموريسكيين في المجتمع فقد كان الحراك الاجتماعي محدودا،وغالبا ماكان ينظر الى المسلمين الذين اعتنقوا الاسلام بعين الريبة من قبل المسيحيين واخوانهم المسلمين على حد سواء.وقد ادى هذا التهميش المزدوج الى عزلة اجتماعية وصعوبات اقتصادية وصدمات نفسية،مما جعل الاندماج في المجتمع مسالة معقدة جدا. علاوة على ذلك ،عززت محاكم التفتيش القمع الثقافي ،حيث استهدفت اللغة والادب والمؤسسات التعليمية الدينية كالمساجد بشكل ممنهج ،واعاق هذا القمع انتقال المعرفة الثقافية بين الاجيال ،مما ساهم في الاختفاء التدريجي للهوية الاجتماعية الاسلامية المميزة. بشكل عام ،دمرت محاكم التفتيش الإسبانية البنية الاجتماعية للمجتمعات المسلمة، مخلفة اثارا دائمة على الثقة والتماسك الاسري كذلك على الهوية الثقافية والتكامل الاجتماعي ،وقد تردد صدى الصدمة التي عانت منها هذه المجتمعات لأجيال، وشكلت الذاكرة الجماعية للاضطهاد والتهميش. الملخص باللغة الانجليزية: The Social Impact of the Inquisition on Muslim Community The Spanish Inquisition, which started at the end of late 15th century, had very harsh effects on Muslim in Spain, especially the Moriscos—Muslims who were forced to become to Christians. Its main purpose was to make everyone follow the same religion, but this destroyed the social of Muslim communities that had been strong for centuries. One clear effect was the loss of unityinside the community. Muslim neighborhoods, which were once full of culture and religion, became places of fear and control.people no longer trusted each other,because anyone could report them.Many had to hide their faith,which created secrecy and suspicion.Social gatherings,traditions,and religious practices were limited,and this made the bonds between people weaker The Inquisition also caused family fragmentation. Many Moriscos were imprisoned, exiled, or executed, leaving families broken and destabilized. Children grew up under constant fear, often receiving Christian education instead of their ancestral Islamic teachings. Intermarriage pressures and forced conversions altered family structures, further eroding traditional social norms. Another significant impact was the marginalization of Moriscos in wider society. Social mobility was limited, and Muslims who outwardly converted were often viewed with suspicion by both Christians and fellow Muslims. This double marginalization created social isolation, economic difficulties, and psychological trauma, making integration into the broader society extremely challenging. Furthermore, the Inquisition fostered cultural suppression, as Islamic language, literature, and educational institutions were systematically targeted. This suppression hindered intergenerational transmission of cultural knowledge, contributing to the gradual disappearance of distinct Muslim social identity. In short,the Spanish inquisition broke the social structure of Muslim communities,affecting trust,families,culture,and their place in society.The pain of this experience stayed with them for generations and became part of their shared memory of suffering.